Un nuevo testimonio de posible culto a Cossus en el Bierzo - García Martínez, Sonia María; Barcia Merayo, Emilio (Estudios humanísticos. Geografía, historia y arte, 1998)
In this article, it’s analized a votive roman inscription from Villasumil (León, Spain), that perhaps it’s consecrated to the indigeous god Cossus.